2010
DOI: 10.2225/vol13-issue6-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and transcriptome profiling of expansin genes isolated from Calotropis procera fibers

Abstract: The Calotropis procera seed fibers provide an excellent model system to study the genes involved in fiber elongation, fineness and strength. Expansins constitute one of the important gene families involved in plant cell expansion and other cell wall modification processes. Four homologs of Expansin A gene i.e. CpEXPA1, CpEXPA2, CpEXPA3 and CpEXPA4 were isolated from the cDNA library obtained from fast growing Calotropis procera fibers. These homologs represented typical Expansin A family. Each of them had two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
4
1
Order By: Relevance
“…The 25-105 fruits per plant obtained in this study was relatively high compared to [10] average of 23 fruits per plant. [22], in a study on flowering and fruiting ecophysiology of C. procera, reported an even lower number of ripened fruits that ranged between 4-18 fruits/plant.…”
Section: B Fruiting Of the Three Provenances Of C Proceracontrasting
confidence: 47%
See 2 more Smart Citations
“…The 25-105 fruits per plant obtained in this study was relatively high compared to [10] average of 23 fruits per plant. [22], in a study on flowering and fruiting ecophysiology of C. procera, reported an even lower number of ripened fruits that ranged between 4-18 fruits/plant.…”
Section: B Fruiting Of the Three Provenances Of C Proceracontrasting
confidence: 47%
“…The observed 1-3 fruits per flower cluster noted in this study has also been documented elsewhere. For example, [10] reported that the fruit number of C. procera varies from 1-3 per inflorescent.…”
Section: B Fruiting Of the Three Provenances Of C Proceramentioning
confidence: 99%
See 1 more Smart Citation
“…It may be assumed that the fiber cell elongation in C. procera is turgor pressure driven by aquaporin activity in cooperation with other fiber-related gene families like expansins, lipid transfer proteins, tubulins, arabino-galactan proteins, and actins (Cheema et al, 2010;Indrais et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It produces long and fine fibers on its seeds for wind dispersal. C. procera fibers can reach up to 45 mm in length (Cheema et al, 2010).…”
Section: Introductionmentioning
confidence: 99%